PENGARUH LATIHAN DEPTH JUMP TERHADAP HASIL LAY UP SHOOT PEMAIN BASKET DI SMAN 10 BEKASI - Ayu Putri Apreliani (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Basketball game is a sport that is demanded by various people but in some games still found unsatisfying achievement because of the player cannot score optimally. One of techniques that’s important in scoring is lay up shoot. Exercise that can be done to enhance lay up shoot score is depth jump exercise. This study aims to identify the impact of depth jump exercise to lay up shoot score enhancement. The design of this study is pre-experimental with pretest-posttest one group design. The population in this study is basketball player of SMAN 10 Bekasi with depth jump exercise 3 times a week. Frequencies of the lay up shoot score from each participant was noted before and after depth jump exercise for 6 weeks. This study uses parametric paired sample t-test to identify the difference between the frequencies of lay up shoot score before and after. Confidence interval that’s used isα = 0,05. The results of data analysis shows that the average of lay up shoot score requencies is 4,25 time, after the exercise is 6,55 times with ρ = 0,000, that statistically meaningful. Therefore, it can be concluded that depth jump exercise can enhance the score of lay up shoot significantly.